2021
DOI: 10.21203/rs.3.rs-783452/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Paclitaxel Chemotherapy Induces Long-Term Memory Impairment and Neuroinflammation in a Mouse Model of Breast Cancer Survivorship

Abstract: BackgroundCancer-related cognitive impairment (CRCI) has been reported in cancer survivors 20 years or more after cancer treatment, and has been associated with sustained increases in circulating inflammatory biomarkers. One of the major risk factors for CRCI is chemotherapy, and preclinical studies typically examine the impact of chemotherapy in cancer naïve mice to evaluate potential mechanisms However, clinical evaluation of the long-term effects of chemotherapy cannot avoid the potential cumulative impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…Animal models have played an indispensable role in further elucidating mechanisms of chemotherapy-induced cognitive impairment that cannot be easily assessed in humans and in helping the future direction of clinical research (20). Studies in mouse models of breast cancer also reported chemotherapy-induced cognitive impairment, associated with neurogenesis, neuroinflammation, and oxidative stress (49,(79)(80)(81)(82).…”
Section: Discussionmentioning
confidence: 99%
“…Animal models have played an indispensable role in further elucidating mechanisms of chemotherapy-induced cognitive impairment that cannot be easily assessed in humans and in helping the future direction of clinical research (20). Studies in mouse models of breast cancer also reported chemotherapy-induced cognitive impairment, associated with neurogenesis, neuroinflammation, and oxidative stress (49,(79)(80)(81)(82).…”
Section: Discussionmentioning
confidence: 99%